1996
DOI: 10.1103/physrevc.53.1221
|View full text |Cite
|
Sign up to set email alerts
|

High spin states inLu164

Abstract: High spin states in the odd-odd 164 Lu nucleus have been investigated for the first time, through in-beam gamma-ray spectroscopy, following the 150 Sm͑ 19 F,5n͒ reaction at beam energy E lab ϭ105 MeV. Four bands, including two signature split bands are identified. The interpretation of the experimental results is discussed in comparison with the existing data in the neighboring nuclei and in the framework of the cranked shell model. The h 11/2 i 13/2 yrast band exhibits anomalous signature splitting and signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…2) Together with the identical bands in 171{175 Ta (Z ¼ 73), 1) such rare cases of identical bands between odd-Z and odd-odd isotopes are quite contrasting to the usual cases observed between odd-Z and even-even isotones at both normal deformation and superdeformation. 6,7) For a band of h 11=2 coupled to h 9=2 in a lighter 164 Lu nucleus, 3,4) the neutron AB band crossing was observed to be unusually delayed in comparison with neighboring nuclei. The two cases of the band built upon g 7=2 or h 11=2 coupled to h 9=2 have been known to have this anomalous band crossing to date.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…2) Together with the identical bands in 171{175 Ta (Z ¼ 73), 1) such rare cases of identical bands between odd-Z and odd-odd isotopes are quite contrasting to the usual cases observed between odd-Z and even-even isotones at both normal deformation and superdeformation. 6,7) For a band of h 11=2 coupled to h 9=2 in a lighter 164 Lu nucleus, 3,4) the neutron AB band crossing was observed to be unusually delayed in comparison with neighboring nuclei. The two cases of the band built upon g 7=2 or h 11=2 coupled to h 9=2 have been known to have this anomalous band crossing to date.…”
Section: Introductionmentioning
confidence: 96%
“…On the experimental side, spectroscopic data for their high-spin states should be available as the oddodd Lu isotopes are considered as good candidates. Previous high-spin studies were reported on 160 Lu, 10) 162 Lu, 11) 164 Lu, 3,4) 166 Lu 12) and 170 Lu. 13) However, high-spin studies on 168 Lu were completely absent until our short report was published.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation